Quality, inequality and recent education reform - Tan, Edita A. (2017)
This paper presents the structure of the country’s educational system in terms of its composition, financing, quality, and distribution. It provides a perspective on why the most recent education initiatives in the Philippines are misdirected. The present quality of education offered by the large majority of schools, both public and private, is shown to be poor by any standard. Of particular concern is the small number of universities that offer science and technology programs especially at the graduate level. Adding years of schooling and expanding the curriculum in basic education, the K-12 program, only further diverts resources from addressing the more fundamental quality issues plaguing the system. In higher education, affording universal free tuition in state universities and colleges fails to address the real reasons for low college attendance among the poor. Such a move similarly draws resources and policy focus away from the more urgent need to promote higher education in science and technology. The paper instead suggests strategies for raising the quality of education and developing science and technology programs.
Keywords: Basic education -- Government policy; Higher education -- Government policy